Bioaccumulation in Functionally Different Species: Ongoing Input of PCBs with Sediment Deposition to Activated Carbon Remediated Bed Sediments. (10th September 2019) - Gidley, Philip T.; Kennedy, Alan J.; Lotufo, Guilherme R.; Wooley, Allyson H.; Melby, Nicolas L.; Ghosh, Upal; Burgess, Robert M.; Mayer, Philipp; Fernandez, Loretta A.; Schmidt, Stine N.; Wang, Alice P.; Bridges, Todd S.; et al.
Abstract: Activated carbon‐amended bed sediments reduced total polychlorinated biphenyl (PCB) accumulation in 3 functionally different marine species, sandworms ( Alitta virens ), hard clams ( Mercenaria mercenaria ), and sheepshead minnows ( Cyprinodon variegatus ), during both clean and contaminated ongoing sediment inputs. Mesocosm experiments were conducted for 90 d to evaluate native, field‐aged bed sediment PCBs, and ongoing input PCBs added 3 times a week. Simulated in situ remediation applied an activated carbon dose equal to the native organic carbon content that was premixed into the bed sediment for 1 mo. The highest bioaccumulation of native PCBs was in worms that remained in and directly ingested the sediment, whereas the highest bioaccumulation of the input PCBs was in fish that were exposed to the water column. When periodic PCB‐contaminated sediment inputs were introduced to the water column, the activated carbon remedy had minimal effect on the input PCBs, whereas the native bed PCBs still dominated bioaccumulation in the control (no activated carbon). Therefore, remediation of only the local bedded sediment in environmental systems with ongoing contaminant inputs may have lower efficacy for fish and other pelagic and epibenthic organisms. While ongoing inputs continue to obscure remedial outcomes at contaminated sediment sites, the present study showed clear effectiveness of activated carbon amendment remediation on native PCBs despite these inputs but no remediation effectiveness for the input‐associated PCBs (at least within the present study duration). Environ Toxicol Chem 2019;38:2326–2336. Published 2019 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.